Phenotypic and genetic parameter estimates for grasscutter production traits. 2. Genetic and phenotypic correlations - S.Y. Annor; B.K. Ahunu; G.S. Aboagye; K. Boa-Amponsem; J.P. Cassady (Global Journal of Food and Agribusiness Management, 2022)
The objective of this work was to estimate genetic and phenotypic correlations among traits of the grasscutter. The study was conducted at the grasscutter section of the Department of Animal Science Education, University of Education, Winneba, Ghana, from 2005 to 2010. Data consisted of records of 502 kids born by 136 does and 40 sires over a period of 5 years. Data were analyzed by mixed model methodology using a full animal model and all known genetic relationships, in multiple trait analysis, using MTDFREML programme. Genetic correlations among size traits (body weight and growth rate) were medium to high (0.32 to 0.87), whilst their phenotypic correlations ranged from low to high (0.01 to 0.99). Antagonistic genetic relationship existed between size and reproductive traits. Phenotypic relationships between size and reproductive traits, survival, feed intake and feed efficiency were not important. Genetic correlations between size traits and survival ranged from no relationship (r = 0.00) to high (r = 0.80). Whilst genetic relationship between feed intake and size traits was positive, that between size traits and feed efficiency was negative. Litter size had little or no genetic relationship with pre-weaning survival but intermediate positive genetic relationship with post-weaning survival. Litter size had little phenotypic relationship with survival but pre-weaning survival had a high positive phenotypic relationship with litter size at weaning. In conclusion, findings in this study were in general agreement of what pertains to the grasscutter and other farm livestock species.